2011
DOI: 10.1002/cctc.201100054
|View full text |Cite
|
Sign up to set email alerts
|

S‐Selective Mixed Carboligation by Structure‐Based Design of the Pyruvate Decarboxylase from Acetobacter pasteurianus

Abstract: The thiamine diphosphate (ThDP)‐dependent pyruvate decarboxylase from Acetobacter pasteurianus (ApPDC) catalyzes the carboligation of aldehydes that yields (R)‐2‐hydroxy ketones with high chemoselectivity in mixed carboligations of aliphatic donor and aromatic acceptor aldehydes. On the basis of the crystal structure of ApPDC, which was determined to a resolution of 2.75 Å, and biochemical data, we mapped the active site. This enabled us to design variants with tailor‐made catalytic activities by modifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 46 publications
(59 reference statements)
0
21
0
3
Order By: Relevance
“…With the exception of a few functionally relevant residues that have been identified by comparing sequences and structures of homologous proteins or by mutation experiments, the molecular basis of this biochemical diversity is still unknown. Variants have been developed by rational design and by directed evolution, in order to improve the activity of members of this enzyme family [16,20,21] or to alter substrate specificity [22-28] or stereoselectivity [29-31]. Some functionally relevant amino acids are located in the active site, mediating substrate binding [3], are involved in the activation of ThDP [28] or steer stereoselectivity [29-31], e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the exception of a few functionally relevant residues that have been identified by comparing sequences and structures of homologous proteins or by mutation experiments, the molecular basis of this biochemical diversity is still unknown. Variants have been developed by rational design and by directed evolution, in order to improve the activity of members of this enzyme family [16,20,21] or to alter substrate specificity [22-28] or stereoselectivity [29-31]. Some functionally relevant amino acids are located in the active site, mediating substrate binding [3], are involved in the activation of ThDP [28] or steer stereoselectivity [29-31], e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Variants have been developed by rational design and by directed evolution, in order to improve the activity of members of this enzyme family [16,20,21] or to alter substrate specificity [22-28] or stereoselectivity [29-31]. Some functionally relevant amino acids are located in the active site, mediating substrate binding [3], are involved in the activation of ThDP [28] or steer stereoselectivity [29-31], e.g. the S -pocket as part of the acceptor binding site, which has been shown to contribute to the stereoselectivity of several members of the decarboxylase superfamily [29-31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The archetypal member of this group is pyruvate decarboxylase (PDC), which catalyzes the nonoxidative decarboxylation of pyruvate to yield acetaldehyde and carbon dioxide, a reaction critical to the fermentation pathway of several yeast and bacteria [2]. X-ray structures of PDCs from a variety of species show that, in addition to ThDP, the active site contains two ionizable acidic residues as well as two contiguous histidine residues that are located on an ordered loop [3][4][5][6]. The latter has been termed the HH-motif, and mutagenesis and kinetic studies have revealed that both histidines play significant roles in catalysis [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Catalysts 2016, 6,190 3 of 16 As with many ThDP-dependent decarboxylases, BFDC and PDC are both are capable of stereoselective carboligation reactions leading to chiral α-hydroxy ketones [26]. These have been used as versatile building blocks in the pharmaceutical (and other) industries [26][27][28].…”
Section: Introductionmentioning
confidence: 99%